Impact of barriers to challenges in education faced by children in a development-induced displaced population resettled in Semmencherry - Mohanambigai, Mohanambigai; N., Rajavel (Edelweiss Applied Science and Technology, 2025)
The studies on the impacts of development projects negatively affect the socioeconomic situations of families; it also leads to an imbalance in the educational system for children. The R&R packages have been given to the families; however, they are not maintained or administered in a reasonable manner. Internal displacement affects livelihoods, destroys family and community structures, impacts education, nutrition, and healthcare, and undermines traditional social norms, making children particularly vulnerable. The relocation of children may have a detrimental impact on their future, academic achievement, and health. This research aims to provide a thorough analysis of the consequences that forcibly removing children from their educational environment has on them. Many people were evacuated to make way for elevated express highway projects in Chennai, Tamil Nadu, and were rehabilitated in Semmencherry. The aim of this study is to find out the impact of barriers to challenges in education faced by children in a development-induced displaced population resettled in Semmencherry. In this study, data were collected from 119 children, of which 57 are males and 62 are females. The sampling method used for this study is the lottery method. The findings show that there is a significant impact on the barriers to challenges in education faced by children in a development-induced displaced population resettled in Semmencherry.